2016
DOI: 10.1111/and.12525
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pregnancy outcome for infertile couples attending IVF and ICSI programmes

Abstract: The purpose of this study was to evaluate the predictors of pregnancy outcome for infertile couples attending in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI) programmes. Infertile couples attending IVF or ICSI procedures were included in this study. Related data including semen parameters and male and female age and body mass index were collected and analysed. The main outcome was clinical pregnancy, defined as an ultrasound detection of foetal heartbeat 6 weeks after embryo transfer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…As summarized in Table 1, several studies have attempted to identify clinical SDF cut-offs for the prediction of natural or ART-related pregnancy [126][127][128][129][130][131]. Although there remains no unanimous consensus on a specific cut-off value, a recent meta-analysis suggests that a cut-off of 20% can potentially differentiate between fertile and infertile men [108].…”
Section: What Test Should I Order?mentioning
confidence: 99%
“…As summarized in Table 1, several studies have attempted to identify clinical SDF cut-offs for the prediction of natural or ART-related pregnancy [126][127][128][129][130][131]. Although there remains no unanimous consensus on a specific cut-off value, a recent meta-analysis suggests that a cut-off of 20% can potentially differentiate between fertile and infertile men [108].…”
Section: What Test Should I Order?mentioning
confidence: 99%
“…Since the middle and late abortion rate were not significantly different among the groups, we suggested that the difference in results was mainly due to the increased early abortion rate of the CryoloopTM group. Many studies have confirmed the female age as an independent predictor for outcomes of IVF (Zhang et al 2016;Loendersloot et al 2010). Although the higher age in the CryoloopTM group (33.29 ± 4.71 years vs. 31.96 ± 4.27 years for CryotopTM, and 31.3 ± 4.28 years for CryoleafTM, p < 0.05) may contribute to a higher early abortion rate, it cannot completely explain the increase of more than 15%.…”
Section: Resultsmentioning
confidence: 99%
“…Infertile men appear to have more genomes impaired than fertile males [23,24]. Analysis of the heterogeneity of sperm DNA as an indicator of the outcome of an ART attempt (IVF or ICSI) has been extensively reported on in recent years [6,[25][26][27]. Indeed, several studies: such as the meta-analysis for Simon et al, 2017 [28] highlight the role of the male genome in the artificial reproductive stages, particularly during fertilization and early embryonic development.…”
Section: Discussionmentioning
confidence: 99%